Métodos otimizados para inversão completa das formas de onda em 3D - Duarte, Edwin Humberto Fagua (2021)
Full waveform inversion (FWI) is one of the most studied techniques today to recover subsurface parameters that affect wave propagation. One of the main difficulties in applying FWI in 3D seismic surveys is its high computational cost. This problem has been solved with the advancement of computational technology, but there are still difficulties to apply FWI to real 3D data. In this work are studied strategies to optimize FWI, which are based on the physical properties of waves. To this end, this work was done in two parts. In the first part, the encoded simultaneous sources technique was used, in which the FWI gradient is calculated by simultaneously propagating information from several sources grouped in one or several subgroups, taking advantage of the superposition principle of the wave equation. In order to reduce the crosstalk noise that appears in the gradient calculation using simultaneous sources, two encoding schemes have been proposed, by phase rotation and by static limited to a period of the dominant frequency. In phase rotation encoding a phase rotation is applied to each shot where the rotation angle is chosen randomly for each shot. In static coding the traces of each shot are temporally shifted and the value of this shift is chosen randomly for each shot having a maximum value of one period of the dominant frequency of the data. With the help of numerical tests on synthetic 2D data to demonstrate that the proposed schemes have a faster convergence than encodings by polarization (multiply by +1 or -1 randomly each shot) and by static without being limited. In the second part, a workflow was developed to apply a FWI to real data acquired in the Brazilian pre-salt region. This data was obtained with an Ocean Bottom Node (OBN) 3D acquisition, where the receivers are placed on the ocean bottom. In the developed workflow, several existing techniques are combined to optimize the use of memory and processing, which take advantage of wave propagation properties. On the OBN data inversions were made using source and receiver decimation strategies to reduce computational cost. The encoded source schemes studied in the first part were also tested. These tests also use various objective functions to try to improve the resolution of the inversions. It was verified that the inversions retrieved information related to the pre-salt reservoir and that both decimation and source coding strategies reduced the computational cost of FWI without compromising the quality of the inversion.